Unveiling Waqf’s Role and Impact on Society Welfare: Deep Study from Indonesia - Ahmad Faisal; Suhail; Imam Nur Aziz; Tufail Hussain (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2024)
Background: Waqf plays an important role in the social life of the people and the Muslim community(Suryana, Ikram & Agustina, 2020) especially in the efforts to combat the poverty because of the scarcity of jobs and. Waqf which success in the history of Islam proves that Islam is able to provide solutions to social security and welfare to its adherents. Waqf in Islamic history is not only a pillar of the welfare of society or individuals, more than that waqf have become a pillar of the nation's economy in building the infrastructure, economy and durability. Objectives: This study analyzes the waqf’s role and impact on society welfare throughout world history and makes a deep study from Indonesia Novelty: Waqf’s role and impact are proven in building three major aspects of human life: economy, knowledge and human resources. Research Methodology / Design: Using triangulation method to increase the credibility and validity of the results by cross-verifying data from different sources or approaches. Findings: We find that waqf’s role and impact always develop from era to era. Waqf’s role in Indonesia has existed since Sultanate era. Masjid, pesantren and university are the most prominent institutions in developing waqf as a tool to enhance society welfare in modern era Implication: Based on the research, this research implications for waqf in unveiling waqf’s role and impact more specific and accurate can be consideration to make waqf as an important tool to enhance micro and macro aspects.